2008
DOI: 10.1038/sj.bjc.6604774
|View full text |Cite
|
Sign up to set email alerts
|

TEAD1 and c-Cbl are novel prostate basal cell markers that correlate with poor clinical outcome in prostate cancer

Abstract: Prostate cancer is the most frequently diagnosed male cancer, and its clinical outcome is difficult to predict. The disease may involve the inappropriate expression of genes that normally control the proliferation of epithelial cells in the basal layer and their differentiation into luminal cells. Our aim was to identify novel basal cell markers and assess their prognostic and functional significance in prostate cancer. RNA from basal and luminal cells isolated from benign tissue by immunoguided laser-capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 56 publications
(52 reference statements)
4
74
1
1
Order By: Relevance
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 72%
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 72%
“…Recent biochemical and genetic studies have established TEAD as a key downstream mediator of YAP (mammalian homolog of Yki) activity and distribution in Hippo signaling Zhao et al, 2008;Zhang et al, 2009). TEAD1 has also been implicated in prostate and pancreatic cancer (Hucl et al, 2007;Kwon et al, 2007;Knight et al, 2008). .…”
Section: Tead/tef Family Transcriptional Factorsmentioning
confidence: 99%
“…CBL is overexpressed in human prostate cancer tissues and increased protein level of CBL was associated with decreased patient survival. 18 Taken together with our finding that CBL is frequently overexpressed in the human breast cancers, it is likely that increased expression of CBL may also be oncogenic. The fact that knockdown of CBL in PC3 prostate cancer cells decreased proliferation is very interesting.…”
Section: Discussionmentioning
confidence: 51%
“…The fact that knockdown of CBL in PC3 prostate cancer cells decreased proliferation is very interesting. 18 It raises an interesting question of whether CBL also functions as a negative regulator of TGF-b signaling in PC3 cells. CBL exerts its functions either through E3 ligase activity or as an adaptor to recruit other molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation